ID: 232. Issue 1 (November 2015) - Köster, Mario; Wolfsmüller, Markus; Kemper, Lucas; Bhushal, Sudeep; Selvakumar, Tharini Ashtalakshmi; Shin, Danim; May, Tobias; Hornef, Mathias; Hauser, Hansjörg
<x xml:space="preserve">Abstract</x> Type I interferons (IFNs) are key cytokines in the innate immune response mediating the first line of defense against a broad range of pathogens. Similar biological effects are reported for type III IFNs, but their full biological activity is restricted to cells of endothelial and epithelial origin. Similarities are based on the employment of canonical Jak/STAT signaling by both types of IFN despite the use of distinct receptors. We characterized the response to type I and type III IFN in mouse intestinal epithelial cells (IEC) and in small intestinal organoid cultures. Reporter-based single cell analysis shows that both IFN types induce a heterogeneous pattern of ISG induction with distinct expressing and non-expressing subpopulations. However, IFN restimulation experiments indicate that a memory is established leading to an increased frequency of ISG induction in the responding subpopulation. Signaling analysis indicates towards a decision making event that is beyond STAT nuclear translocation. We identified histone acetylation as an enhancer of IFN-lambda activity but not of IFN-beta signaling. Importantly, IFN-lambda-dependent gene induction is hardly affected by inhibition of histone deacetylase activity under 3D cultivation conditions. Polarization of IECs equalizes the strength and robustness of type I and type III IFN signaling and emphasizes the importance of cell culture conditions on cell intrinsic properties. Together, these results indicate that in contrast to IFN-beta, IFN-lambda signaling is adjustable and depends on cell intrinsic properties related to epithelial organization.